2005
DOI: 10.1097/01.rlu.0000186855.03752.9d
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous Left Ventricular Cavity Size Measurements on Myocardial Perfusion SPECT Resulting From Transient Arrhythmias

Abstract: Transient ischemic dilatation (TID) of the left ventricle during stress on myocardial perfusion imaging is a sign of severe coronary artery disease. Factors other than ischemia can transiently influence left ventricular size, however, and TID ratios can be misleading if these factors are not properly identified. We describe 4 cases of stress-rest Tc-99m sestamibi SPECT myocardial perfusion imaging in which both abnormally high and low TID ratios were seen as a result of the presence of transient supraventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Elevated TID measures have also been correlated with cardiac events in individuals with normal perfusion patterns [14]. Since average left ventricular cavity volume is influenced by heart rate (faster heart rate leading to smaller volumes due to reduced filling time) it is possible that TID measurements may be affected by normal change in heart rate between the stress and rest images.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated TID measures have also been correlated with cardiac events in individuals with normal perfusion patterns [14]. Since average left ventricular cavity volume is influenced by heart rate (faster heart rate leading to smaller volumes due to reduced filling time) it is possible that TID measurements may be affected by normal change in heart rate between the stress and rest images.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the acute rebound effect of HR after abrupt beta blockers withdrawal [28] as part of the preparation for the stress test can potentially influence the first acquisition, but may be already attenuated on the second day, which can cause TID if rest imaging is performed first at a higher HR. Transient supraventricular tachyarrhythmias at rest have also been identified as a cause of 'false' TID [19]. Additionally, it should be noted that using 99mTc-MIBI, post-stress acquisition takes place several minutes after test cessation (which is not the case with 201-Thallium or even stress echocardiography, where imaging is performed immediately after stress).…”
Section: Discussionmentioning
confidence: 99%
“…However, technical factors potentially affecting LV volume calculations are rarely considered as a cause of TID in otherwise normal studies. In fact, it has been reported that many cases of TID could be explained by apparent volumetric changes secondary to differences in heart rate (HR) at the time of acquisition of the post-stress and rest portions of the procedure, but there is very scarce literature on this matter, and study populations were not homogeneous [17][18][19]. We proposed to assess the correlation between TID and HR in patients with no perfusion defects, no previous history of CAD, and without other objective factors potentially affecting LV volume determination.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Transient arrhythmias, both tachy-and bradyarrhythmias, during the acquisition can produce falsely elevated or reduced TID measurements. Elevated HR during poststress acquisition can be due to continued effects of exercise or pharmacological stress, or due to temporarily withdrawal of negative chronotrophic medication.…”
Section: Hr Dependencementioning
confidence: 97%